2014
DOI: 10.1093/mnras/stu1737
|View full text |Cite
|
Sign up to set email alerts
|

Three newly discovered sub-Jupiter-mass planets: WASP-69b and WASP-84b transit active K dwarfs and WASP-70Ab transits the evolved primary of a G4+K3 binary★†

Abstract: We report the discovery of the transiting exoplanets WASP-69b, WASP-70Ab and WASP-84b, each of which orbits a bright star (V ∼ 10). WASP-69b is a bloated Saturn-mass planet (0.26 M Jup , 1.06 R Jup ) in a 3.868-d period around an active, ∼1-Gyr, mid-K dwarf. ROSAT detected X-rays 60±27 ′′ from WASP-69. If the star is the source then the planet could be undergoing mass-loss at a rate of ∼10 12 g s −1 . This is 1-2 orders of magnitude higher than the evaporation rate estimated for HD 209458b and HD 189733b, both… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 61 publications
7
71
0
Order By: Relevance
“…Finally, WASP-107b is a 0.12-M Jup planet in a 5.7-day orbit around a K6 star. Together with WASP-139b (M P = 0.12 ± 0.02 M Jup ; Hellier et al 2016), WASP-107b is the lowest-mass planet discovered by WASP to date; the next lowest are WASP-29b (0.24 M Jup ; Hellier et al 2010) and WASP-69b (0.26 M Jup ; Anderson et al 2014). Giant planets seem to be more common around both stars of higher metallicity and stars of higher mass (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, WASP-107b is a 0.12-M Jup planet in a 5.7-day orbit around a K6 star. Together with WASP-139b (M P = 0.12 ± 0.02 M Jup ; Hellier et al 2016), WASP-107b is the lowest-mass planet discovered by WASP to date; the next lowest are WASP-29b (0.24 M Jup ; Hellier et al 2010) and WASP-69b (0.26 M Jup ; Anderson et al 2014). Giant planets seem to be more common around both stars of higher metallicity and stars of higher mass (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…For example, WASP-84b is in a relatively wide orbit around a young star, indicating that it has experienced relatively weak tidal forcing over a short duration. Therefore, its near-circular and near-aligned orbit is suggestive of disc migration (Anderson et al 2014(Anderson et al , 2015b. Further, WASP-47 comprises a hot Jupiter, a nearby super-Earth, a nearby Neptune, and a more distant Jupiter.…”
Section: The Migration Of Short Period Giant Planetsmentioning
confidence: 99%
“…Only a few planetary systems are known around stars with log R HK > −4.5. They include hot Jupiters such as WASP-52b, 59b, or 84b Anderson et al 2014), giant planets on longer periods such as HD 192263b, GJ 3021b, and HD 81040b (Santos et al 2000a;Naef et al 2001;Sozzetti et al 2006), or the multi-planet systems around HD 128311 and HD 9446 (Vogt et al 2005;Hébrard et al 2010). The new giant planet HD 12484b increases this population.…”
Section: Hd 12484mentioning
confidence: 99%
“…The observational and analysis techniques used here are similar to those in recent WASP-South discovery papers (e.g., Hellier et al 2012;Anderson et al 2014), and so are reported briefly. WASP-South surveys the southern sky using an array of 200 mm f/1.8 lenses and a cadence of ∼10 minutes (see Pollacco et al 2006).…”
Section: Observationsmentioning
confidence: 99%